Synthesis and Crystal Structure of 5,5’-Dimethoxy-2,2’-[(hexane-1,6-diyldioxy)bis(nitrilomethylidyne)]diphenol - Liu, Xin-Wen; Zhang, Yang; Zhang, Yu-Jie; Li, Gang; Wang, Li; Dong, Xiu-Yan (Asian Journal of Chemistry, 2013)
The chelating bis-oxime compound i.e., 5,5'-dimethoxy-2,2'-[(hexane-1,6-diyldioxy)bis(nitrilomethylidyne)]diphenol with the molecular formula C22H28N2O6, assumes an E configuration with respect to the azomethine C=N bond and the two phenyl rings are parallel to each other. There are two fairly strong intramolecular O2-H2···N1 and O5-H5···N2 hydrogen bonds. Each compound molecule links four other neighboring molecules through three pairs of intermolecular C11-H11C···O5 and C18-H18···O6 hydrogen-bonding interactions into an infinite wave-like 2D-layer supramolecular structure.